Minecraft : medieval fortress - Jelley, Craig (Del Rey, 2016)
"Learn how to design, build, and customize every part of your castle and the surrounding area, from sturdy walls and deadly traps to dank, dark dungeons and sprawling villages. Each build has an exploded view to show you exactly which blocks to use, plus extra ideas to make every part of your kingdom unique"--Back cover.